“The Old Wild West in the New Middle East”: American Sniper (2014) and the Global Frontiers of the Western Genre - Lennart Soberon (European Journal of American Studies)
Clint Eastwood’s war film American Sniper (2014), based on the autobiography of (in)famous Navy Seals sniper Chris Kyle, was met on release with considerable commercial success and political controversy. This article investigates how through adopting generic structures and binary oppositions of the classic Western film American Sniper succeeds in evoking a sense of “frontier mythology.” By generically restructuring historical events, American Sniper analogizes the Iraq War with the mythic struggle of civilization/wilderness and portrays Kyle as a trailblazing frontiersman leading the way to Western expansion. Such a mythical conception of the Western genre operates as a political frame through which a jingoist discourse on the Iraq war is reaffirmed and within which audiences can interpret the conflict—and the undertaken military measures—as necessary and just.